Centralization and decentralization: Evaluation of marine and coastal management models and performance in the Northwest Pacific Region. (October 2016) - Lin, Wan-Ni; Wang, Nuo; Song, Nan-Qi; Lu, Yue
Abstract: The marine and coastal management (MCM) in various coastal countries is closely related to the national political systems, history, economic development and maritime strategies of the countries. No region in the world embodies as many differences as the Northwest Pacific Region (NWPR). Against this complex background, this paper comparatively analyses the institutional arrangement and legal system of the MCM in this region, summarizes the characteristics and divides the five coastal countries around the NWPR into two models: the MCM of China and ROK belongs to centralization, and the MCM of Japan, DPRK, and Russia belongs to decentralization. To evaluate the MCM performance in the five countries, this paper establishes an indicator framework from the four elements of the institutional arrangement and management, the legal system, the coastal environment and the ocean economy, and the principal component analysis (PCA) method is employed as the weighting method to synthesize the evaluation results. The evaluation results demonstrate that compared to the other four countries, Japan performed better in terms of the institutional arrangement and management and legal system aspects; DPRK performed best in terms of the evaluation aspects of the coastal environment; and China performed best in terms of the ocean economy aspects. In terms of the general MCM performance, Japan performed best, followed by ROK, China and Russia, with DPRK performing the worst. Overall, the MCM in the NWPR after years of adjustment has been effectual, and the effectiveness of the MCM performance among different countries varies greatly. Regardless of the differences in the current effectiveness of the MCMs of these countries, it is a future trend to improve the coastal environment and develop the ocean economy according to one's own development needs. Finally, the main areas to be improved in the various countries are proposed. Highlights: MCM of five countries in the Northwest Pacific Region were first studied. Characteristics and status of MCM in DPRK were analysed for the first time. We established a new framework of indicators for evaluation of MCM performance.